Health-related quality of life in children with biliary atresia - Ong, S.Y.; Ng, R.T.; Khoh, K.M.; Lee, W.S. (2014)
BACKGROUND: In children with biliary atresia (BA) who did not have surgery or in those who had an unsuccessful surgery, survival beyond three years of age is rare without liver transplantation (LT). Children with BA who had a successful surgery require long term follow up to detect complications associated with chronic liver disease (CLD).